2022
DOI: 10.3390/ph15010084
|View full text |Cite
|
Sign up to set email alerts
|

Mangostanin, a Xanthone Derived from Garcinia mangostana Fruit, Exerts Protective and Reparative Effects on Oxidative Damage in Human Keratinocytes

Abstract: The fruit of Garcinia mangostana (mangosteen) is known in ancient traditional Asian medicine for its antioxidant, anti-inflammatory, immunomodulatory and anticancer activities. These effects are mainly due to the action of polyphenols known as xanthones, which are contained in the pericarp of the fruit. In recent years, there has been a growing interest from pharmaceutical companies in formulating new topicals based on mangosteen full extracts to prevent skin aging. However, the molecules responsible for these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…An earlier study has reported that FRA regulates TGF-β signaling in fibrotic liver disease [168] , which hints therapeutic potential of FRA in treating cancer, as both are characterized by the accumulation of myofibroblasts. A recent report demonstrated that FRA-loaded nanoparticle inhibits the CAF phenotype by impeding TGF-β signaling in PDAC [169] . Mangostin (MG) is a xanthone and exhibits several medicinal properties such as antibacterial, antifungal, antioxidant, anti-inflammatory, anticancer, and cardioprotective effects [170] .…”
Section: Targeting Cafs With Natural Products and Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study has reported that FRA regulates TGF-β signaling in fibrotic liver disease [168] , which hints therapeutic potential of FRA in treating cancer, as both are characterized by the accumulation of myofibroblasts. A recent report demonstrated that FRA-loaded nanoparticle inhibits the CAF phenotype by impeding TGF-β signaling in PDAC [169] . Mangostin (MG) is a xanthone and exhibits several medicinal properties such as antibacterial, antifungal, antioxidant, anti-inflammatory, anticancer, and cardioprotective effects [170] .…”
Section: Targeting Cafs With Natural Products and Analogsmentioning
confidence: 99%
“…A recent report demonstrated that FRA-loaded nanoparticle inhibits the CAF phenotype by impeding TGF-β signaling in PDAC [ 169 ] . Mangostin (MG) is a xanthone and exhibits several medicinal properties such as antibacterial, antifungal, antioxidant, anti-inflammatory, anticancer, and cardioprotective effects [ 170 ] . Studies have demonstrated that MG displays antitumor activities by inducing apoptosis and inhibiting angiogenesis, ECM modification, and EMT [ 171 ] .…”
Section: Targeting Cafs With Natural Products and Analogsmentioning
confidence: 99%
“…In this case, the xanthone derivative in the form of alpha-mangostin (αM) is the main component (Maligan et al, 2019). The seeds and pericarp are mainly used empirically, including for treating gastrointestinal and urinary tract infections, laxatives, anti-fever agents, and treatment of insomnia (Abate et al, 2022). It has an activity as an antitumor, anti-inflammatory, and antioxidant.…”
Section: Salvia Fruticosa Millmentioning
confidence: 99%
“…It has been used as a medicinal plant ( Nauman & Johnson, 2022 ). Mangosteen pericarp (MP) is an important source of bioactive xanthones, which has remarkable antioxidant, anti-inflammatory, immunomodulatory, antiviral, antifungal, antibacterial, and anticancer activities ( Abate et al, 2022 ; Nauman & Johnson, 2022 ). In literature, G. mangostana extract and α-mangostin have previously shown anti- Acanthamoeba activity and anti-adhesion properties against Acanthamoeba triangularis ( Sangkanu et al, 2021 ; Sangkanu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%